Are there benefits to being naked? The returns and diversification impact of capital structure arbitrage - Maggie Chen (The European Journal of Finance, 2013)
In a naked credit default swap (CDS) position a party pays an income stream to a seller of protection to swap away default risk on an underlying defaultable security without actually holding this reference instrument. Using mark to market returns on a large cross section of CDS positions, held independently from their reference entity, we implement a novel test to establish whether their inclusion in an optimised portfolio is replicable by a large set of alternative assets. Overall, we nd signi cant excess returns of over 28% per annum against an optimised benchmark, we speculate that it is these characteristics that could be driving a bubble in the CDS market.